Histories of archaeology : a reader in the history of archaeology - Murray, Tim, 1955-; Evans, Christopher, 1955- (Oxford University Press, 2008)
A collection of 19 reprinted papers by distinguished scholars, Histories of Archaeology reflects the growing interest in the historiography of this discipline. A general introduction orients readers by outlining core themes and issues in the field. - ;In recent years there has been an upsurge of interest in the history of the discipline of archaeology. Local, national, and international histories of archaeology that deal with institutions, concepts, categories, and the social and political contexts of archaeological practice have begun to influence the development of archaeological theory. Thi.